Finding the Relationship Between the Biological Dagradtion Rate Constants and Some of the Calculated Physical Properties of a Number of Carcinogenic poly Aromatic Hydrocarbons - Rayan Mahmood; Zaheda Najim (College of Education for Pure Sciences, 2019)
This study involves the theoretical calculation of binding energy (the free energy ΔG°) of eleven of polycyclic aromatic hydrocarbons (PAHs) compounds with catechol 1,2-dioxygenase enzyme from the gram-positive Rhodococcus opacus (3HGI) enzyme that is used for degrading these types of compounds and also identifies the values of binding energy that compactable with constant values of biological degradation rate. It is noted that binding energy inversely proportional with rate constants and binding energy (R=0.951), as the binding energy with enzyme are increased, the degradation rate are decreased. The study observes that binding energy values were ranging between ([-5.051] - [-7.12] Kcal/mol) whereas values of root mean squared deviation (RMSD) were ranging between (1.12-1.71A°) by which accurate results have been confirmed depending on previous studies. The study also determines the amino acids that surround the compounds which are usually blinded by the hydrogen bond or hydrophobic interactions types π-π. Finally, the study obtains a three - dimensional shape of compound's binding with enzyme of its more stable shape. Also obtains the shapes of distribution of the electronic cloud on the compound and amino acids that are surrounding them in which getting locations around the studied compound's molecule depending on their features of an amino acid (acidity - basic - hydrophobic). MOE (Molecular Operating Environment) is used for this step of calculation.